Synthesis, Optical, Magnetic and Thermodynamic Properties of Rocksalt Li1.3Nb0.3Mn0.4O2 Cathode Material for Li-Ion Batteries - Mohamed Kamel; Abanoub R. N. Hanna; Cornelius Krellner; Rüdiger Klingeler; Mohamed Abdellah; Mahmoud Abdel-Hafiez; Arafa Hassen; Ahmed S. G. Khalil; Tarob Abdel-Baset; Abdelwahab Hassan (Crystals, 2021)
Since the discovery of the reversible intercalation of lithium-ion materials associated with promising electrochemical properties, lithium-containing materials have attracted attention in the research and development of effective cathode materials for lithium-ion batteries. Despite various studies on synthesis, and electrochemical properties of lithium-based materials, fairly little fundamental optical and thermodynamic studies are available in the literature. Here, we report on the structure, optical, magnetic, and thermodynamic properties of Li-excess disordered rocksalt, Li1.3Nb0.3Mn0.4O2 (LNMO) which was comprehensively studied using powder X-ray diffraction, transient absorption spectroscopy, magnetic susceptibility, and low-temperature heat capacity measurements. Charge carrier dynamics and electron–phonon coupling in LNMO were studied using ultra-fast laser spectroscopy. Magnetic susceptibility and specific heat data are consistent with the onset of long-range antiferromagnetic order at the Néel temperatures of 6.5 (1.5) K. The effective magnetic moment of LNMO is found to be 3.60 <semantics>μB</semantics>. The temperature dependence of the inverse magnetic susceptibility follows the Curie–Weiss law in the high-temperature region and shows negative values of the Weiss temperature 52 K (3), confirming the strong AFM interactions.